The impact of the coronavirus pandemic on patients hospitalized due to acute coronary syndrome - Jankowska-Sanetra, Justyna; Sanetra, Krzysztof; Synak, Magdalena; Milewski, Krzysztof; Gerber, Witold; Buszman, Piotr Paweł (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2023)
The coronavirus disease 2019 (COVID-19) pandemic significantly increased mortality worldwide. However, only part of the excess mortality is related directly to the infection. Local healthcare accessibility, time to reach medical care and patients’ reluctance to seek medical aid strongly affected the treatment results in many fields. The current report aims to analyze mortality and morbidity in patients who suffered from acute coronary syndrome (ACS) during the COVID-19 pandemic, as well as to investigate the factors that may have a significant impact on their baseline characteristics and outcome. Multiple reports were evaluated. Most of them point to reluctance and longer time to reach medical care, longer pre-hospital delay, lower overall number of ACS admissions, greater percentage of ST-elevation myocardial infarction patients and complications. Younger and less ill patients were more likely to suffer from ACS than in the pre-pandemic period. They presented with more prominent biomarker elevation. Further, the number of invasive procedures dropped significantly, which was most prominent in the field of surgical revascularization. Consequently, a higher number of adverse events and greater mortality during the COVID-19 pandemic were noted, which was valid for both patients with and without coronavirus infection. In summary, the pandemic had a great impact on overall populational mortality and morbidity, which was greatly pronounced in patients with cardiovascular disease, particularly in ACS cases. They differed in baseline characteristics, underwent different treatment and their outcome was worse as compared with the period prior to the pandemic.